The comic book style of the poetical subject in the contemporary Croatian poetry of intermedial and postintermedial experience - Jukić, Sanja (Poznańskie Studia Slawistyczne, 2012)
This  paper  deals  with  poetic  subjects  in  the  comic  book  format  as  presented  in  the media. The subject of media entity  dominates the corpus of texts in  intermedial and post-intermedial poetry experience. These aspects of Croatian poetry from 1968 up to the present day,  whose structures  are  primarily  determined  by  contacts  with  different  media  culture texts,  are  defined by  Goran  Rem.  This  paper  explores  the  ways  in  which  the  media  inter-mediates comic book semiotics into the poetic code of that particular part of contemporary Croatian poetry and thus determines the paradigmatic forms of the subject of media/comic book.